Strength of ships and ocean structures / Alaa Mansour, Donald Liu ; J. Randolph Paulling, editor - Mansour, Alaa; Liu, Donald (Principles of Naval Architecture series, 2008)
This volume addresses several topics of ship strength in greater depth than in the previous edition of PNA, bringing much of the material up to date and introducing some new subjects. There is extensive coverage of the latest developments in dynamic sea load predictions, including nonlinear load effects, slamming and impact plus new sections on the mechanics of collisions and grounding.